CO2 methanation over ordered mesoporous NiRu-doped CaO-Al2O3 nanocomposites with enhanced catalytic performance. (4th January 2018) - Liu, Qing; Wang, Shengjia; Zhao, Guoming; Yang, Hongyuan; Yuan, Meng; An, Xiaoxi; Zhou, Haifeng; Qiao, Yingyun; Tian, Yuanyu
Abstract: The ordered mesoporous NiRu-doped CaO-Al2 O3 nanocomposites were synthesized via a facile evaporation-induced self-assembly method for CO2 methanation. Metallic Ni and Ru species retained the single-component heterostructure rather than NiRu alloy over the 600 °C-reduced catalysts. Owing to the synergistic effect of bimetallic Ni–Ru as well as the improved H2 and CO2 chemisorption capacities after the addition of Ru and CaO promoters, the ordered mesoporous 10N1R2C-OMA catalyst exhibited enhanced catalytic activity and selectivity, which achieved the maximum CO2 conversion of 83.8% and CH4 selectivity of 100% at 380 °C, 0.1 MPa, 30000 mL g −1  h −1 . In a 550 °C-109 h-lifetime test, the ordered mesoporous 10N1R2C-OMA catalyst showed high stability and superior anti-sintering property due to the confinement effect of the ordered mesostructure. Graphical abstract: Highlights: Ordered mesoporous RuNi-doped CaO-Al2 O3 nanocomposites were synthesized by EISA method. RuNi-doped CaO-Al2 O3 catalyst exhibited high activity and stability in CO2 methanation. Addition of Ru resulted in increased H2 chemisorption. Addition of CaO species intensified the CO2 chemisorption. The confinement effect of the ordered mesostructure increased the stability.